Structural Studies of Nicotinic Acetylcholine Receptors: Using Acetylcholine‐Binding Protein as a Structural Surrogate. Issue 6 (14th January 2016) - Shahsavar, Azadeh; Gajhede, Michael; Kastrup, Jette S.; Balle, Thomas
Abstract: Nicotinic acetylcholine receptors (nAChRs) are members of the pentameric ligand‐gated ion channel superfamily that play important roles in the control of neurotransmitter release in the central and peripheral nervous system. These receptors are important therapeutic targets for the development of drugs against a number of mental health disorders and for marketed smoking cessation aids. Unfortunately, drug discovery has been hampered by difficulties in obtaining sufficiently selective compounds. Together with functional complexity of the receptors, this has made it difficult to obtain drugs with sufficiently high‐target to off‐target affinity ratios. The recent and ongoing progress in structural studies holds promise to help understand structure–function relationships of nAChR drugs at the atomic level. This will undoubtedly lead to the design of more efficient drugs with fewer side effects. As a high‐resolution structure of a nAChR is yet to be determined, structural studies are to a large extent based on acetylcholine‐binding proteins (AChBPs) that despite low overall sequence identity display a high degree of conservation of overall structure and amino acids at the ligand‐binding site. Further, AChBPs reproduce relative binding affinities of ligands at nAChRs. Over the past decade, AChBPs have been used extensively as models for nAChRs and have aided the understanding of drug receptor interactions at nAChRs significantly.